2021
DOI: 10.1007/s15010-020-01559-5
|View full text |Cite
|
Sign up to set email alerts
|

Different types of bullae of limbs with necrotizing fasciitis predict different outcome: a prospective study

Abstract: Study objective Necrotizing fasciitis (NF) is an uncommon life-threatening necrotizing skin and soft tissue infection. Bullae are special skin manifestations of NF. This study was conducted to analyze the differences between different types of bullae of limbs with NF for providing the information to emergency treatment. Methods From April 2015 to August 2018, patients were initially enrolled based on surgical confirmation of limbs with NF. Accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Wang et al reported that 68% patients developed hemorrhagic bullae on the fourth day; however, our patients commonly presented with hemorrhagic bullous skin lesions upon arrival to the ER [ 5 ]. Thus, the appearance of hemorrhagic bullae was an important diagnostic criteria for NF in our institution, especially in those patients with Vibrio and Aeromonas infections [ 7 , 8 , 9 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Many of the literature had proved that Gram-negative NF had a significant higher prevalence of bloodstream infections than Gram-positive NF [ 9 , 13 , 14 , 15 , 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Wang et al reported that 68% patients developed hemorrhagic bullae on the fourth day; however, our patients commonly presented with hemorrhagic bullous skin lesions upon arrival to the ER [ 5 ]. Thus, the appearance of hemorrhagic bullae was an important diagnostic criteria for NF in our institution, especially in those patients with Vibrio and Aeromonas infections [ 7 , 8 , 9 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Many of the literature had proved that Gram-negative NF had a significant higher prevalence of bloodstream infections than Gram-positive NF [ 9 , 13 , 14 , 15 , 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the appearance of hemorrhagic bullae was an important diagnostic criteria for NF in our institution, especially in those patients with Vibrio and Aeromonas infections [ 7 , 8 , 9 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Many of the literature had proved that Gram-negative NF had a significant higher prevalence of bloodstream infections than Gram-positive NF [ 9 , 13 , 14 , 15 , 28 , 29 , 30 , 31 ]. In this study, we demonstrated that Gram-negative NF with hemorrhagic bullae presentation and bacteremia was significantly associated with poor prognosis, which should be considered first when patients are revealed to have quickly progressing and fulminant features at the ER.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Laboratory tests and radiological imaging have a significant place in the prediction of infection severity and treatment outcome [16,17,18]. This is why scoring systems have been developed as predictors of the severity of infection.…”
Section: Discussionmentioning
confidence: 99%